JAVIER PÉREZ IGUALADA - Arquitecturas comparadas. Observaciones dispersas sobre parecidos razonables / Compared Architectures. Scattered Observations on Reasonable Resemblances - Díez Medina, Carmen (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Javier Pérez Igualada Arquitecturas comparadas. Observaciones dispersas sobre parecidos razonables / Compared Architectures. Scattered Observations on Reasonable Resemblances Valencia: Editorial Universitat Politècnica de València, 2021. 176 pp. Softcover. Language: Spanish / English. 15 € (Ebook 8 €) ISBN: 978-84-9048-293-3